78.2k views
0 votes
Implicit differentiation Please help

Implicit differentiation Please help-example-1
User Rylee
by
5.9k points

2 Answers

6 votes
Hope this helps you with implicit differentiations
Implicit differentiation Please help-example-1
User Scudelletti
by
5.7k points
5 votes

Answer:


y''(-1) =8

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Equality Properties

Algebra I

  • Factoring

Calculus

Implicit Differentiation

The derivative of a constant is equal to 0

Basic Power Rule:

  • f(x) = cxⁿ
  • f’(x) = c·nxⁿ⁻¹

Product Rule:
(d)/(dx) [f(x)g(x)]=f'(x)g(x) + g'(x)f(x)

Chain Rule:
(d)/(dx)[f(g(x))] =f'(g(x)) \cdot g'(x)

Quotient Rule:
(d)/(dx) [(f(x))/(g(x)) ]=(g(x)f'(x)-g'(x)f(x))/(g^2(x))

Explanation:

Step 1: Define

-xy - 2y = -4

Rate of change of the tangent line at point (-1, 4)

Step 2: Differentiate Pt. 1

Find 1st Derivative

  1. Implicit Differentiation [Product Rule/Basic Power Rule]:
    -y - xy' - 2y' = 0
  2. [Algebra] Isolate y' terms:
    -xy' - 2y' = y
  3. [Algebra] Factor y':
    y'(-x - 2) = y
  4. [Algebra] Isolate y':
    y' = (y)/(-x-2)
  5. [Algebra] Rewrite:
    y' = (-y)/(x+2)

Step 3: Find y

  1. Define equation:
    -xy - 2y = -4
  2. Factor y:
    y(-x - 2) = -4
  3. Isolate y:
    y = (-4)/(-x-2)
  4. Simplify:
    y = (4)/(x+2)

Step 4: Rewrite 1st Derivative

  1. [Algebra] Substitute in y:
    y' = (-(4)/(x+2) )/(x+2)
  2. [Algebra] Simplify:
    y' = (-4)/((x+2)^2)

Step 5: Differentiate Pt. 2

Find 2nd Derivative

  1. Differentiate [Quotient Rule/Basic Power Rule]:
    y'' = (0(x+2)^2 - 8 \cdot 2(x + 2) \cdot 1)/([(x + 2)^2]^2)
  2. [Derivative] Simplify:
    y'' = (8)/((x+2)^3)

Step 6: Find Slope at Given Point

  1. [Algebra] Substitute in x:
    y''(-1) = (8)/((-1+2)^3)
  2. [Algebra] Evaluate:
    y''(-1) =8
User Akash Bhandwalkar
by
5.3k points